Skin cancer screening: recommendations for data-driven screening guidelines and a review of the US Preventive Services Task Force controversy. (March 2017) - Johnson, Mariah M; Leachman, Sancy A; Aspinwall, Lisa G; Cranmer, Lee D; Curiel-Lewandrowski, Clara; Sondak, Vernon K; Stemwedel, Clara E; Swetter, Susan M; Vetto, John; Bowles, Tawnya; Dellavalle, Robert P; Geskin, Larisa J; et al.
Melanoma is usually apparent on the skin and readily detected by trained medical providers using a routine total body skin examination, yet this malignancy is responsible for the majority of skin cancer-related deaths. Currently, there is no national consensus on skin cancer screening in the USA, but dermatologists and primary care providers are routinely confronted with making the decision about when to recommend total body skin examinations and at what interval. The objectives of this paper are: to propose rational, risk-based, data-driven guidelines commensurate with the US Preventive Services Task Force screening guidelines for other disorders; to compare our proposed guidelines to recommendations made by other national and international organizations; and to review the US Preventive Services Task Force's 2016 Draft Recommendation Statement on skin cancer screening.